Trade, law and culture: an analysis of supranationality in international commerce - Marzouka Devilat, Marcelo (Estudios Internacionales, 2021)
The paper studies the emergency of supranational organizations in international commerce, its legal nature and its effect in the trade of its member States, controlling by historical and cultural affinity between countries, which would facilitate legal, linguistic, symbolic and social codes, as well as social capital. Quantitative methodology is used, with a simple random sampling method, forming 189 dyads of States, with a non-experimental design of transversal temporality (year 2006). The results suggest that the effect of supranational organizations is heterogeneous and that the effect of the historical and cultural affinity varies for language, religion and former colonialism relations.